Development of a Wavelength‐Shifting Fluorescent Module for the Adenosine Aptamer Using Photostable Cyanine Dyes. Issue 2 (12th February 2015) - Walter, Heidi-Kristin; Bohländer, Peggy R.; Wagenknecht, Hans-Achim
Abstract DNA‐based aptamers are commonly used recognition elements in biosensors for a range of target molecules. Here, the development of a wavelength‐shifting optical module for a DNA‐based adenosine‐binding aptamer is described. It applies the combination of two photostable cyanine‐styryl dyes as covalent modifications. This energy‐transfer pair is postsynthetically attached to oligonucleotides via a copper(I)‐catalyzed azide–alkyne cycloaddition by two structurally different approaches: 1) as nucleotide modifications at the 2′‐position of uridines and 2) as nucleotide substitutions using (S)‐amino‐1, 2‐propanediol as acyclic linker between the phosphodiester bridges. Both dyes exhibit a remarkable photostability. A library of DNA aptamers consisting of different combinations of the two dyes in diagonal orientations were evaluated by their emission color contrast as readout. Further optimization led to aptasensors with improved fluorescent readout as compared with previously reported aptasensors. This approach described is synthetically facile using simple propargylated phosphoramidites as DNA building blocks. As such, this approach could be applied for other dyes and other chemical/biological applications.